Sejarah Sosial Adat dan Budaya Lokal Masyarakat Desa Cikate: Sebuah Studi Kualitatif - Deri alamsyah Deri (Journal of Citizenship, 2025)
Abstract : This study aims to analyze the sustainability of customary tradition systems and the mechanisms of socio-religious harmonization in Cikate Village, Malingping District, Lebak Regency, Banten. Using a qualitative approach with participatory ethnography methods, this research deeply explores ritual practices such as Seren Tahun, earth alms (sedekah bumi), and pilgrimage, while reconstructing local historical narratives that form the basis of customary legitimacy. Talcott Parsons' Structural Functionalism theory and Emile Durkheim's Social Cohesion concept are employed as analytical frameworks to understand how social subsystems (customs, religion, and social structure) interact functionally to maintain societal equilibrium. The findings indicate that customary traditions in Cikate Village not only survive as cultural heritage but function actively as social integration mechanisms producing strong mechanical solidarity amid modernization. The kesepuhan system serves as a latent institution (Latency) that maintains collective value patterns and norms, while deliberative consensus practices create social cohesion through shared emotional experiences. Key findings demonstrate that the customary-religious relationship in Cikate Village confirms a pattern of harmonious syncretism not assimilation that erases identity, but accommodation that maintains functional differentiation between elements. System integration is strengthened by emotional bonds (we-feeling), shared moral commitments, and functional interdependence between customary elders, religious figures, and the community. This research confirms that local cultural sustainability requires institutions capable of performing adaptation functions to external changes without losing core identity. The theoretical implications enrich understanding of customary system survivability in universal religion contexts, while practical contributions provide a model for community-based cultural preservation policy development. Keywords: customary traditions, kesepuhan, social cohesion, structural func